Effect of Differentiation and Satisfaction on Tourist Promotion of Historical Tourism: Role of using AR Technology - Boonsong, Ratchadaporn; Meesumrarn, Thiraphat; Torasa, Chonmapat (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The current study examined the relationship between differentiation, satisfaction, tourist loyalty, AR technology and tourism promotion in relation to the historical tourism. The objective of this study is to examine the role of differentiation and satisfaction in tourism promotion. Additionally, the moderating role of AR technology was examined. Population of the current study was the employees of tourism management companies in Thailand. By using a survey questionnaire, 300 questionnaires were distributed among the employees of tourism management companies in Thailand. Results of the study found that differentiation has positive effect on tourism promotion. Differentiation also has positive effect on tourism loyalty. Satisfaction has positive effect on tourism promotion. Additionally, satisfaction also has positive effect on tourist loyalty. Moreover, tourist loyalty and AR technology has positive effect on tourism promotion.